The role of Alexey Butovsky in the development of physical education, sport and Olympic Movement. - Bubka S.N (Kharkov National Pedagogical University, 2012)
Presents is an analysis of role of activity of A.D. Butovsky, his labours and ideas in development in Russia of physical education, sport and Olympic Movement at the end of XIX - at the beginning of XX centuries. The contribution of A.D. Butovsky is considered to the theory and practice of domestic physical education during his service on different positions in Main administration of soldiery educational establishments and on results foreign business trips. The results of generalization of experience are rotined during the stay of A.D. Butovsky in composition the International Olympic Committee and on different international congresses (1905 and 1910). Positions of A.D. Butovsky and P.F. Lesgaft are presented on the different applied aspects of physical education. The organizational aspects of preparation and participation of sportsmen of Russia are selected on the Olympic Games. Attitude of Russian society is marked toward practical realization of olympic ideas in a country.